Field Reports: Yes, They Will Add to the Prehospital and Disaster Knowledge Base. Issue 4 (24th May 2016) - Fattah, Sabina; Rehn, Marius; Wisborg, Torben
Abstract : S Fattah, M Rehn, T Wisborg .Field reports: yes, they will add to the prehospital and disaster knowledge base .Prehosp Disaster Med .2016 ;31 (4 ):461 –461 .